Intervensi Psikoedukasi Kecanduan Gadget Pada Murid Sit Al-Fathanah - Nurul Fitriani; Adhim Vayla Rahmadio Mijaya; Ad'ha Ramadhani; Iqlimatul Inayah Ya’kub; Muhrajan Piara; Irdianti Irdianti (CV. Ulil Albab Corp, 2023)
Gadget is a term used to refer to various types of technological tools that are growing rapidly and have special functions, such as smartphones, iPhones, computers and tablets. Gadgets are in great demand by various groups, both adults and children, because of their sophistication. Too frequent and excessive use of gadgets can cause addictive effects. This service activity is in the form of psychoeducation which is carried out at MI SIT AL-Fathanah. The psychoeducational method used is the lecture method with the aim of making it an effort for children to understand the impact of gadget addiction as well as giving pre-tests before lectures and post-tests after giving lectures. The results of the insights that have been given show that there is a change in students' knowledge after education is given. The expected benefits after carrying out this education are knowledge for students, especially children who often play gadgets.